Synthesis and Application of Jatropha Oil based Polyurethane as Paint Coating Material - Harjono, Harjono; Sugita, Purwantiningsih; Mas’ud, Zainal Alim (Makara Journal of Science, 2012)
Recently, the use of renewable sources in the preparation of various industrial materials has been revitalized in response to environmental concerns. Natural oils are considered to be the most important genre of renewable sources. Jatropha curcas oil (JPO) based polyol is an alternative material that may possibly replace petrochemical-based polyol for polyurethane coating material. Polyurethane was synthesized by reacting JPO-based polyol with isocyanate. To produce JPO-based polyol, JPO was first epoxidized to form epoxidized J. curcas oil (EJP), subsequently it was converted to polyol by the opening ring reaction with acrylic acid (AA) using triethylamine (TEA) as a catalyst. The JPO-based polyurethane film resulting from this study is compared with polyurethane film from commercial polyol for gloss, hardness, and adhesion quality. The result showed that the source of polyol has an influence on gloss, hardness, and adhesion of polyurethane film, but the differences with using isocyanate has less influence. Using visual observation, polyurethane film produced from L.OHV polyol, H.OHV polyol and commercial polyol have similar quality.